Recombination signal sequence binding protein Jkappa is constitutively bound to the NF-kappaB site of the interleukin-6 promoter and acts as a negative regulatory factor. - Plaisance, S (1997)
Analysis by electrophoretic mobility shift assays (EMSA) of the different proteins associated with the kappaB sequence of the interleukin-6 (IL-6) promoter (IL6-kappaB) allowed us to detect a specific complex formed with the recombination signal sequence binding protein Jkappa (RBP-Jkappa). Single-base exchanges within the oligonucleotide sequence defined the critical base pairs involved in the interaction between RBP-Jkappa and the IL6-kappaB motif. Binding analysis suggests that the amount of RBP-Jkappa protein present in the nucleus is severalfold higher than the total amount of inducible NF-kappaB complexes but that the latter bind DNA with a 10-fold-higher affinity. A reporter gene study was performed to determine the functional implication of this binding; we found that the constitutive occupancy of the IL6-kappaB site by the RBP-Jkappa protein was responsible for the low basal levels of IL-6 promoter activity in L929sA fibrosarcoma cells and that RBP-Jkappa partially blocked access of NF-kappaB complexes to the IL-6 promoter. We propose that such a mechanism could be involved in the constitutive repression of the IL-6 gene under normal physiological conditions.